Metagenomic insights into the relationship between gut microbiota and residual feed intake of small-sized meat ducks - Bai, Hao; Shi, Lei; Guo, Qixin; Jiang, Yong; Li, Xiaofan; Geng, Dandan; Wang, Chenxiao; Bi, Yulin; Wang, Zhixiu; Chen, Guohong; Xue, Fuguang; Chang, Guobin (Frontiers in Microbiology, 2023)
The objective of this study was to determine the regulatory effects of gut microbiota on feed efficiency (FE) of small-sized meat ducks through evaluating correlations between gut microbiota and the residual feed intake (RFI). A total of 500 healthy 21-day-old male ducks with the similar initial body weight (645 g ± 15.0 g) were raised contemporaneously in the same experimental facility until slaughter at 56 days of age. Nine low RFI (LR) and nine high RFI (HR) birds were selected for further gut microbiota composition and functional analysis based on the production performance and the calculated RFI from 22 to 56 days of age. Growth performance results indicated significant lower RFI, feed conversion ratio, feed intake, and average daily feed intake in the LR ducks (P < 0.05). Taxonomy results of gut microbiota showed an identification of 19 kinds of phyla and more than 250 kinds of genera in all samples. No significant discrepancies of cecal bacterial α-diversity were discovered between the LR and HR groups, which indicated that the microbial modulatory effects on RFI may attribute to the bacteria composition rather than the species diversity. Differential analysis on bacterial communities between the LR and HR groups showed a significant increment of Firmicutes, while a significant decline of Bacteroidetes in the LR group (P < 0.05). Specifically, genera of Erysipelatoclostridius, Parasutterella, Fournierella, and Lactococcus significantly proliferated while the Bacteroides significant decreased in the LR group (P < 0.05). Further, correlation analysis showed RFI was significantly correlated with carbohydrate metabolism-related bacteria including Bacteroides, Alistipes, Bifidobacterium, Ruminiclostridium_9, Sellimonas, Oscillibacter, Escherichia-Shigella, Lactococcus, and Streptococcus. In conclusion, the communities that related to carbohydrate metabolism performed positive regulatory effects on FE, which can promote the FE of small-sized meat ducks by improving the relative abundance and utilization of these communities. The present study provides valuable insight into the dynamics of gut microbiota underlying the variations in FE of small-sized meat ducks.